“I’ll burn my books” : Doctor Faustus, and the closing emblem of a powerless man - Goh, Ondrea Xin Yi (2017)
This paper will firstly locate the concept of power in the text, and demonstrate how the human desire for power motivates the acquisition of knowledge. That said, the presence of an omnipotent supernatural realm in 'Doctor Faustus' essentially means that the degree of agency possessed by Man is ultimately constrained by forces beyond human control, which throws the human notion of power into question. In light of this, my paper will proceed to discuss the restricted scope of Man’s jurisdiction over his life. While Man can amass power in its varying forms, he invariably has no choice over the field of options within which he may freely choose. Owing that 'Doctor Faustus' is so steeped in Christian ideology, I will endeavour in a textual analysis that cross-references with the Bible, in a bid to trace these allusions to creation, grace and damnation that the play deals with, and how it relates to Fasutus’ pursuit of power.